2018
DOI: 10.1161/circulationaha.118.034621
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and NLRP3 Inflammasome Activation Initiated in Response to Pressure Overload by Ca 2+ /Calmodulin-Dependent Protein Kinase II δ Signaling in Cardiomyocytes Are Essential for Adverse Cardiac Remodeling

Abstract: Background: Inflammation is associated with cardiac remodeling and heart failure, but how it is initiated in response to non-ischemic interventions in the absence of cell death is not known. We tested the hypothesis that activation of CaMKIIδ in cardiomyocytes in response to pressure overload elicits inflammatory responses leading to adverse remodeling. Methods: Mice in which CaMKIIδ was selectively deleted from cardiomyocytes (CMs) (Cardiac specific knockout; CKO) and floxed control (CTL) mice were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
193
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(214 citation statements)
references
References 51 publications
19
193
0
2
Order By: Relevance
“…Previous studies have shown that CaMKII activated Drp1 via phosphorylation at Ser 616 and an increase in Drp1 translocation to the mitochondria induced excessive mitochondrial fragmentation [53,54]. Our data showed that CaMKII activated by ethanol- Many studies have reported that an increase in intracellular calcium induces inflammasome formation and CaMKII signaling triggers inflammasome activation in cardiomyocytes [55][56][57]. These results suggest that CaMKII signaling is important for inflammasome activation.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have shown that CaMKII activated Drp1 via phosphorylation at Ser 616 and an increase in Drp1 translocation to the mitochondria induced excessive mitochondrial fragmentation [53,54]. Our data showed that CaMKII activated by ethanol- Many studies have reported that an increase in intracellular calcium induces inflammasome formation and CaMKII signaling triggers inflammasome activation in cardiomyocytes [55][56][57]. These results suggest that CaMKII signaling is important for inflammasome activation.…”
Section: Discussionsupporting
confidence: 70%
“…The role of the NLRP3 inflammasome in cardiac diseases has been increasing recognized [113][114][115] and recent evidence further suggests that NLRP3 inflammasome activation occurs in cardiomyocytes within the heart [113,116,117]. For instance, our recent studies have shown that the NLRP3 inflammasome is activated in cardiomyocytes in response to angiotensin-II or pressure overload and that this contributes to recruitment of immune cells, cardiac fibrosis, and ventricular dysfunction [116,118]. Involvement of inflammasome signaling in cardiac disease has also been suggested by clinical findings using interventions that inhibit IL-1β function or block the IL-1 receptor [119,120].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…Recently, accumulating evidence has suggested that the NLRP3 inflammasome, composed of apoptosis‐associated speck‐like protein containing a CARD (ASC), caspase‐1 and NLRP3, has been recognized as an important mediator of the inflammatory response (Franchi, Eigenbrod, Muñoz‐Planillo, & Nuñez, 2009; Sutterwala et al., 2006). Notably, activation of the NLRP3 inflammasome participates in several cardiovascular‐related inflammatory process (Abderrazak et al., 2015; Gan et al, 2017; Suetomi et al., 2018). Activation of the NLRP3 inflammasome requires NF‐κB signalling (Bauernfeind et al., 2009).…”
Section: Discussionmentioning
confidence: 99%